1983
DOI: 10.1017/s0043174500069198
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Grain Sorghum (Sorghum bicolor) from Chloroacetanilide Herbicide Injury

Abstract: CGA-43089 [α-(cyanomethoximino)-benzacetonitrile] seed treatment was evaluated at three Nebraska locations during 1979 and 1980 for grain sorghum [Sorghum bicolor(L.) Moench] protection from injury by metolachlor [2-chloro-N-(2-ethyl-6-methylphenyl)-N-(2-methoxy-1-methylethyl)acetamide], four other chloroacetanilide herbicides, and three metolachlor +s-triazine combinations. Acetochlor [2-chloro-N-(ethoxymethyl)-6′-ethyl-o-acetotoluidide] caused the most frequent and severest injury to unprotected and protecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…However, our greenhouse results show that atrazine at 1.12 kg/ha reduced growth of grain sorghum in the absence of any visible damage. Although studies showed that cyometrinil can protect grain sorghum against damage by metolachlor and alachlor (11,29), some reports indicated these herbi cides reduced grain sorghum growth even in the presence of this safener (15,17). Our results agree with those of the latter and show that metolachlor and alachlor caused re ductions in all growth parameters that were determined at plant maturity (Table 2).…”
Section: • Control • Atrazi Ne E3 M E T O L a C H L O R E3 Atr + M E supporting
confidence: 90%
“…However, our greenhouse results show that atrazine at 1.12 kg/ha reduced growth of grain sorghum in the absence of any visible damage. Although studies showed that cyometrinil can protect grain sorghum against damage by metolachlor and alachlor (11,29), some reports indicated these herbi cides reduced grain sorghum growth even in the presence of this safener (15,17). Our results agree with those of the latter and show that metolachlor and alachlor caused re ductions in all growth parameters that were determined at plant maturity (Table 2).…”
Section: • Control • Atrazi Ne E3 M E T O L a C H L O R E3 Atr + M E supporting
confidence: 90%
“…Acetochlor + 2,4-D, cyanazine + aceto chlor, and cyanazine at 2.7 kg/ha reduced stands when ap plied at planting but not when applied 25 or 45 days prior to planting (Table 2). Acetochlor at 3.4 kg/ha reduced sor- ghum stands in other research in Nebraska on soil where the seedbed was prepared by tillage (8). Apparently the seed safener CGA-92194 was not satisfactory in protecting the sorghum seed from acetochlor injury, but it did provide protection from alachlor and metolachlor injury.…”
Section: Sorghum Populationmentioning
confidence: 80%
“…Herbicides need to be applied several days ahead of planting in order to spread the workload and reduce weed control problems. Safeners have become available to protect sorghum seed from acetanilide injury (5,8), which allows use of these herbicides that effectively control grass weeds.…”
Section: Introductionmentioning
confidence: 99%
“…There are no published reports of these specific herbicides causing injury to white oaks but all have caused injury to other plant species. Preemergent applications of acetochlor have injured sorghum [Sorghum bicolor (L.) Moench] (Roeth et al, 1983). Chrysanthemum (Chrysanthemum leucantheum L.) and kale and collards (Brassica oleracea L. var.…”
mentioning
confidence: 99%